1999
DOI: 10.1038/sj.bjp.0702575
|View full text |Cite
|
Sign up to set email alerts
|

Role of potassium channels and nitric oxide in the relaxant effects elicited by β‐adrenoceptor agonists on hypoxic vasoconstriction in the isolated perfused lung of the rat

Abstract: 1 The aims of this study were to compare, in the rat isolated perfused lung preparation, the antagonist eects of a nonselective b-adrenoceptor agonist (isoprenaline), a selective b 2 -adrenoceptor agonist (salbutamol) and a selective b 3 -adrenoceptor agonist (SR 59104A) on the hypoxic pulmonary pressure response, and to investigate the role of K + channels, endothelium derived relaxing factor and prostaglandins in these eects. K + channels were inhibited by glibenclamide, charybdotoxin or apamin, NO synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Blockade of NO synthesis decreased vasodilation [8]. Other authors [7][8][9] reported that blockade of NO synthesis had no effect on the degree of β 2 -adrenergic vasodilation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Blockade of NO synthesis decreased vasodilation [8]. Other authors [7][8][9] reported that blockade of NO synthesis had no effect on the degree of β 2 -adrenergic vasodilation.…”
Section: Resultsmentioning
confidence: 97%
“…Little is known about the NO-dependent endothelial mechanism of systemic vasodilation. The role of NO in the vascular response to β 2 -adrenoceptor stimulation was studied only on isolated vessels [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Indeed, the effect of various potassium channel blockers on isoprenalinemediated relaxation in rat aorta suggests that BK Ca channels, 11,42 K Ca channels, 42 ATP-sensitive potassium channels 44,45 and voltagesensitive potassium channels 46 may be involved in mediating the b-adrenoceptor relaxant response. Thus, in the present study, the non-selective potassium channel blocker TEA, which has some selectivity for BK Ca channels, 47 was used to examine the involvement of potassium channels in isoprenaline-mediated relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the broad‐spectrum K + channel inhibitors BaCl 2 and tetraethylammonium did not have major effects on vasodilation by sodium nitroprusside, isoprenaline or C2‐ceramide. Although the K ATP channel blocker glibenclamide has been reported to partially inhibit isoprenaline‐induced vasodilation in the hypoxic pulmonary circulation (Dumas et al ., 1999), it did not affect vasodilation by isoprenaline in the present study and also had little if any effect on vasodilation by sodium nitroprusside or C2‐ceramide. Apamine is an inhibitor of SK Ca small conductance K + channels and has been shown to inhibit e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Apamine is an inhibitor of SK Ca small conductance K + channels and has been shown to inhibit e.g. β 3 ‐adrenoceptor‐mediated vasodilation in a perfused hypoxic lung preparations (Dumas et al ., 1999). However, in the present study apamine did not affect vasodilation by isoprenaline or sodium nitroprusside and surprisingly even enhanced vasodilation by C2‐ceramide.…”
Section: Discussionmentioning
confidence: 99%